Revisão sistemática e metanálise: níveis de evidência e validade científica - Gonçalves, Hortência de Abreu (2018)
The systematic review is it a literary research that enables the careful synthesis of available evidence about a particular problem, serving to assist the development of scientific information, with or without meta-analysis. This review article presents the theoretical foundations of systematic review and meta-analysis, highlighting the importance of levels of evidence and validity study the quantitative and the qualitative. He appealed to the survey of digital library resources on these topics in scientific and university databases. It attempted still, the method of analysis of content as a guideline of the study, an explanatory perspective, based on the arguments checked in the investigated sources.